Determination of Rivaroxaban in Human Plasma Samples - Harenberg, Job; Erdle, Sandra; Marx, Svetlana; Krämer, Roland (Seminars in Thrombosis and Hemostasis, 2012)
Rivaroxaban is one of the novel oral direct factor Xa inhibitors, which is effective in preventing thromboembolic complications at fixed doses (i.e., once daily), without the need for dose adjustment according to laboratory monitoring. Nearly 60% of rivaroxaban is cleared from circulation by glomerular filtration, 30% of which is excreted as active drug. Therefore, as renal elimination plays a pivotal role in the metabolism of this drug, impairment of renal function may be important during anticoagulation with rivaroxaban over long periods of time. The assessment of the anticoagulant effect/concentration of rivaroxaban may thus be useful in special patient populations such as in the elderly and eldest, during acute diseases with concurrent dehydration, before surgery, during bleeding or thrombotic episodes, or to verify adherence to therapy. Rivaroxaban prolongs prothrombin time in a dose-dependent, linear fashion. Activated partial thromboplastin time (APTT) is also prolonged, but in an exponential manner. Substantial differences in test results might be generated by different thromboplastin and APTT reagents. One-step prothrombin-induced clotting time assay is sensitive to low concentrations of rivaroxaban. Chromogenic substrate assays specific for factor Xa are also sensitive to rivaroxaban. Several initiatives are currently ongoing to standardize the various methods to determine rivaroxaban in human plasma samples, some of which will be summarized in this article along with the dose-dependent effects of rivaroxaban on relevant coagulation parameters. Therefore, although rivaroxaban prolongs all coagulation assays used to assess the anticoagulant effects of most anticoagulants, the most specific assay cannot be identified at present. Moreover, clinical trials are needed to determine the relationship of assay results with bleeding or thrombotic complications.
Keywords: rivaroxaban; prothrombin time assay; activated partial thromboplastin time; thromboplastin reagent; prothrombinase-induced clotting time assay; chromogenic substrate methods